Emperipolesis in a Case of B-Cell Lymphoma: A Rare Phenomenon Outside of Rosai-Dorfman Disease - Lopes, Lisandro F.; Bacchi, Maura M.; Coelho, Kunie Iabuki Rabello [UNESP]; Filho, Armando Antico; Bacchi, Carlos E. [UNESP] (Elsevier, 2003)
We describe a case of a diffuse large B-cell lymphoma with extensive emperipolesis phenomenon. Light microscopy revealed numerous CD68-positive/S-100-negative histiocytes containing viable neoplastic hematopoietic cells in their cytoplasm. Electron microscopy confirmed these findings. In this case, there was no evidence of Rosai-Dorfman disease either clinically or histologically. This report emphasizes that emperipolesis is not restricted to Rosai-Dorfman disease and can be found in other conditions including non-Hodgkin lymphomas. © 2003 Elsevier Inc. All rights reserved.
Keywords: Electron microscopy; Emperipolesis; Immunohistochemistry; Lymphoma; Rosai-Dorfman disease; antineoplastic agent; CD68 antigen; protein S 100; aged; B cell lymphoma; cancer chemotherapy; cancer regression; case report; cell type; cytoplasm; electron microscopy; emperipolesis; hematopoietic cell; histiocyte; histopathology; human; human tissue; immunohistochemistry; male; microscopy; phagocytosis; priority journal; Rosai Dorfman disease; Aged; Antineoplastic Agents; Cytoplasm; Histiocytosis, Sinus; Humans; Immunoenzyme Techniques; Lymph Nodes; Lymphoma, B-Cell; Male; Treatment Outcome; Tumor Markers, Biological